Analysis of pulmonary sequestration cases, based on the 11-year birth defects surveillance data of Changsha hospitals - Ruobin Xie; Tao-Sha Wang; Yanling Wang; Wei-Dong Wang (Scientific Reports)
Abstract Pulmonary sequestration (PS) is a rare congenital malformation that is characterized by the absence of a connection between a portion of the lung tissue and the tracheobronchial tree, with blood supply from arteries throughout the body. Abnormal lung tissue cannot perform the normal gas exchange function. In the absence of timely diagnosis and early intervention, some cases may need labor induction, and some of the infants who survive may develop symptoms in childhood. The manifestations are repeated lung infections, dry cough, chest pain, chest tightness, and hemoptysis. Some cases have no symptoms in childhood and are misdiagnosed and mistreated because of lung imaging findings in adulthood. Given the scarcity of related literature on PS, this present study aimed to investigate its prevalence, factors affecting survival, and strategies to avoid misdiagnosis and inappropriate treatment in adulthood. Based on our results, we proposed three levels of preventive care for prenatal and postnatal diagnoses and childhood prevention of the complications of PS. The medical records of children diagnosed as PS at all the birth defects monitoring hospitals of Changsha City from January 1, 2013 to December 31, 2023 were retrospectively analyzed. The factors influencing survival were evaluated by univariate and multivariate analyses. Within 11 years, a total of 94 cases were diagnosed as PS, with an prevalence of 0. 989/100,00. The prevalence of PS was highest in the 30–34 age group and among mothers with a college education or above. The number of definitive diagnosis of PS and survivors increased every year. The main factors affecting the survival of children with PS were maternal education level, maternal age of 30–34 years,annual per capita income, number of pregnancies, and the coexistence of other congenital abnormalities. Given the increase in the number of surviving children with PS, the value of prenatal consultation, followed by development of the best treatment plan through timely multidisciplinary consultation after birth, was highlighted. The absence of surgical treatment in childhood should be well documented, in order to avoid future misdiagnosis and inappropriate treatment.